On the Solution of a Class of Toeplitz Systems (Journal of Computational Mathematics, 2021)
The solution of certain Toeplitz linear systems is considered in this paper. This kind of systems are encountered when we solve certain partial differential equations by finite difference techniques and approximate functions using higher order splines. The methods presented here are more efficient than the Cholesky decomposition method and are based on the circulant factorization of the symmetric "banded circulant" matrix, the Woodbury formula and the algebraic perturbation method.